Ticagrelor vs Clopidogrel in Clopidogrel-Naive Patients With Chronic Coronary Syndrome - Manzo-Silberman, Stéphane; Guedeney, Paul; Cayla, Guillaume; Beygui, Farzin; Rangé, Grégoire; Motovska, Zuzana; Procopi, Niki; Kerneis, Mathieu; Zeitouni, Michel; El Kasty, Mohamad; Teiger, Emmanuel; Filippi, Emmanuelle; et al. (JACC. Cardiovascular interventions, 2024)
BACKGROUND: Whether ticagrelor may reduce periprocedural myocardial necrosis after elective percutaneous coronary intervention (PCI) in patients with and without chronic clopidogrel therapy is unclear. OBJECTIVES: This study sought to compare ticagrelor vs clopidogrel in patients with and without chronic clopidogrel therapy before undergoing elective PCI. METHODS: In this prespecified analysis of the ALPHEUS (Assessment of Loading With the P2Y12 Inhibitor Ticagrelor or Clopidogrel to Halt Ischemic Events in Patients Undergoing Elective Coronary Stenting) trial, patients were defined as clopidogrel(+) and clopidogrel(-) according to the presence and absence of clopidogrel treatment for ≥7 days before PCI, respectively. The primary endpoint was the composite of PCI-related myocardial infarction and major injury as defined by the third and fourth universal definition 48 hours after PCI. RESULTS: A total of 1,882 patients were included, 805 (42.7%) of whom were clopidogrel(+). These patients were older, had more comorbidities, and had more frequent features of complex PCI. The primary endpoint was less frequently present in clopidogrel(-) compared to clopidogrel(+) patients (32.8% vs 40.0%; OR: 0.73; 95% CI: 0.60-0.88), but no significant differences were reported for the risk of death, myocardial infarction, stroke, or transient ischemic attack at 48 hours or 30 days. Ticagrelor did not reduce periprocedural myocardial necrosis or the risk of adverse outcomes, and there was no significant interaction regarding the presence of chronic clopidogrel treatment. CONCLUSIONS: Clopidogrel-naive patients presented less periprocedural complications compared to clopidogrel(+) patients, a difference related to a lower risk profile and less complex PCI. The absence of clopidogrel at baseline did not affect the absence of a difference between ticagrelor and clopidogrel in terms of PCI-related complications supporting the use of clopidogrel as the standard of care in elective PCI in patients with or without chronic clopidogrel treatment.
Keywords: hodnocení rizik; ticagrelor; Female; clopidogrel; výsledek terapie; ženské pohlaví; antagonisté purinergních receptorů P2Y; Time Factors; časové faktory; krvácení; lidé; koronární angioplastika; nekróza; Platelet Aggregation Inhibitors; cardiovascular outcomes; Treatment Outcome; Risk Assessment; elective percutaneous intervention; dual antiplatelet therapy; Necrosis; Risk Factors; klopidogrel; Percutaneous Coronary Intervention; Ticagrelor; nemoci koronárních tepen; Male; Purinergic P2Y Receptor Antagonists; Clopidogrel; Aged; Stents; Hemorrhage; Coronary Artery Disease; rizikové faktory; Myocardial Infarction; inhibitory agregace trombocytů; chronická nemoc; lidé středního věku; senioři; mužské pohlaví; chronic coronary syndrome; Chronic Disease; Middle Aged; stenty; infarkt myokardu; Humans